Effect of hill spacings and nitrogen levels on yield and its components of two rice cultivars - Abd El-Raouf, M. S.; El-Metwally, El-M. A.; Ghanem, S. A.; Abd El-Salam, R. M. (2008)
Two field experiments were carried out at Rice Research Training Center, Sakha, Kafr-El-Sheikh Governorate during 2000 and 2001 seasons. The effects of nitrogen levels (0, 23, 46, 69, and 92 kg N/fad) and three hill spacing (15x10, 15x15, and 15x20 cm) on growth, yield and yield components of two rice cultivars (Giza 182 and Sakha 103) were studied. Results showed that: Giza182 cultivar exceeded Sakha103 in plant dry weight, chlorophyll content, panicle length, panicle weight; number of filled prains\panicle, 1000-grain weight and grain yield. On the contrary, Sakha 103 cultivar exceeded Giza 182 in harvest index as well as hulling, milling and head rice percentage. Number of tillers\hill, dry weight of plant\hill, panicle length, number of filled grainslpanicle and grain yield significantly increased with increasing space between hills from 10 to 20 cm. Plant height, number of tillers\hill, plant dry weight, panicle length, number of grains\paniele, panicle grain weight and 1000-grain weight significantly increased as nitrogen level increased up to 92 kg N\fad. However grain yield\fad, hulling, milling and head rice percentage significantly responded only up to 69 Kg Nkfad and further N increase could not show any significant increase in yield. Key words: Rice, Cultivars, Hill spacing, Nitrogen, Growth, Quality, Hulling, Milling
Includes reference.
Summary in Arabic.
1
Keywords: Rice -- Fertilizers; Rice -- Varieties; Rice -- Spacing; Rice -- Yields; Nitrogen fertilizers